Open Strategy as Practice - Soini, Krista (My University, 2025)
To gain or keep competitive advantage companies need to have a vision and strategy. Strategizing has traditionally been the work of top management. However, the pendulum has swift towards more open strategizing during the decades. The open strategy links into strategy work in the form of inclusion and transparency. The study aims to shed some light on the strategy process of a multinational company and the open and closed elements of it. The study builds on strategy-as-practice approach and open strategy concept. It utilizes strategy-as-practice approach as a lens to study open strategy practices. It shows practitioners, praxis and practices involved in the strategy process with an aim to identify open and closed practices of strategizing. It considers openness through inclusions, transparency and participation in decision-making. The empirical single case study is conducted by interviewing 17 participants in the strategy process from the three levels of company structure. The data of semi-structured interviews is analyzed using Nag and Gioia method. It is considered through 1st order concepts, 2nd order themes and aggregate level dimensions. The study presents the top-down and bottom-up process that includes open and closed elements. The process is more open at the strategy analysis and formulation phases whereas it moves towards closed strategizing at the decision-making phase. Once the strategy is approved and the implementation starts, the process becomes open. The contribution of the study is to present an empirical case study of a multinational company with the focus on open strategy practices. It shows six themes and two aggregate level dimensions. The themes are transparency, inclusion, participation in decision-making, strategy, process and management that conclude into the aggregate dimensions of open strategy and the process. The thesis concludes with the theoretical and managerial implications. The study mentions the pros and cons of open strategy and the tensions of open and closed elements. The managerial implications relate to elements of open strategy and the possible finetuning of process. Finally, the thesis mentions the limitations of the study and suggests avenues for future research.
Keywords: strategies; corporate strategies; openness; transparency; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development